2009
DOI: 10.14221/ajte.2009v34n6.4
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Pedagogic Knowledge Base: a Comparison between Experienced and Less Experienced Practitioners

Abstract: Second language teacher education community has become increasingly interested in the pedagogical knowledge base of teachers as a window into practitioners' mental lives. The present study was conducted to document likely differences between the pedagogic thoughts of experienced and less experienced teachers. Eight teachers participated in the project. Data were collected through the use of stimulated recall. The analysis of the data shows that there are differences both in the number and the order of the thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…In addition, the two studies showed that experienced practitioners generated a larger quantity of pedagogical thought units than novices (907 and 819 respectively); however, no statistical comparison was made to determine whether this difference was significant. This was the central concern by Akbari and Tajik (2009) which concluded that experienced ELT teachers produced a significantly larger number of pedagogical thought units, supporting the claim that teaching experience can be an influential factor in enlarging teachers' knowledge base. Mullock (2006) undertook a partial replication of Gatbonton's (1999) study.…”
Section: Teacher Cognitionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, the two studies showed that experienced practitioners generated a larger quantity of pedagogical thought units than novices (907 and 819 respectively); however, no statistical comparison was made to determine whether this difference was significant. This was the central concern by Akbari and Tajik (2009) which concluded that experienced ELT teachers produced a significantly larger number of pedagogical thought units, supporting the claim that teaching experience can be an influential factor in enlarging teachers' knowledge base. Mullock (2006) undertook a partial replication of Gatbonton's (1999) study.…”
Section: Teacher Cognitionmentioning
confidence: 68%
“…Since then, more attention has been paid to teachers' knowledge base and thinking on the grounds that what teachers do in the classroom originates from their mental acts, which have their roots in attitudes, values, knowledge and beliefs collected through their experience as students and teachers (Gatbonton, 1999;Mullock, 2006). Terms such as 'teachers' pedagogical knowledge base' (Shulman, 1987) and 'teacher cognition' (Borg, 2003) grew out of this swing of pendulum to describe thoughts that shape teachers' beliefs about teaching and learning and influence their classroom practices (Akbari & Tajik, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ascertain the extent to which teachers possess the requisite professional knowledge for TEFL, educational researchers have conducted empirical studies in a wide range of areas (e.g., Akbari & Tajik, ; Freeman & Johnson, ; Freeman et al., ; Karimi, ). To date, qualitative studies have tended to explore the domain‐specific challenges EFL teachers face in the process of teaching from a phenomenological perspective (e.g., Baker, ; Baleghizadeh & Shahri, ; Gatbonton, , ; Liu, ; Mullock, ).…”
Section: Teacher Knowledge As An Outcome Of Teacher Preparationmentioning
confidence: 99%
“…These studies, however, encompass a rather small proportion of those realms which are affected by teachers’ beliefs and thought processes. As an incipient research area in the ELT context (Gatbonton, 2008), more studies are needed to investigate the role of teacher cognition in other aspects of the language classroom (Akbari and Dadvand, 2011; Akbari and Tajik, 2009).…”
Section: Introductionmentioning
confidence: 99%